STRATEGI PENGUATAN SEKOLAH AMAN BENCANA GEMPA BUMI JENJANG SEKOLAH MENENGAH ATAS DAN KEJURUAN DI KECAMATAN LEMBANG - Zeny Silvia Futri, - (2020)
The Safe School of Disaster is a government policies to disaster mitigation in education. Responses from students, teachers and schools through policies relating to structural and non-structural aspects have a role each in an effort. The purpose of this study for analyze the level of preparedness of citizens of high school and Vocational in Lembang sub-district against earthquake,aspects structural and analyzing risk strategy for strengthening high school and vocational school for safe schools Earthquake Disasters. The research method used is descriptive, school residents include students, teachers/staff and school principals are the samples in this study. Index and SWOT analysis is used to produce preparedness levels and analyze strategies for strengthening Disaster Safe Schools. The results of the research index are in a ready condition that is 75.63 for students and 72.61 for teachers on the other hand the School index is in a less ready condition that is 44.69. The school community has 66.65 preparedness included in the Ready category. The dominant building structure has been adjusted to the potential for disaster, the design of class structuring, furniture and its contents, the surrounding utilities, the support of infrastructure does not yet have requirements based on BNPB provisions so it has not been said to be safe. Schools with unsafe status based on the above indicators dominate at 66.67%. The position of the disaster safe school strategy is in quadrant III which has weaknesses but still has opportunities.Recomendation of the school not safe yet requires strengthening in the form of improvements in structural components by experts as well as non-structural aspects that is disaster direction policy in school. Keywords: Preparedness, Safe Schools of Disaster, Strengthening Strategies